Sympathetic Nerve Cell Destruction in Newborn Mammals by 6-Hydroxydopamine - Angeletti, P. U. (1970)
A selective and permanent destruction of sympathetic ganglia was achieved by injecting 6-hydroxydopamine in newborn animals. A lifelong chemical sympathectomy may thus be obtained. The process of cell damage and destruction is substantially different from that produced with an antiserum to a specific nerve growth factor.